Environmental Aspects of the State of African Coastal Territories - GRISHINA Nina Vladimirovna (Ученые записки Института Африки Российской академии наук)
To preserve the ecological balance and health of the population of the African continent, it is necessary to maintain the cleanliness of the surrounding rivers, lakes and ocean coasts. Oil production, transportation of oil and petroleum products inevitably lead to pollution of sea waters due to accidents on tankers, equipment breakdowns, and fires.